2016
DOI: 10.3390/toxins8070214
|View full text |Cite
|
Sign up to set email alerts
|

Toxin-Antitoxin Modules Are Pliable Switches Activated by Multiple Protease Pathways

Abstract: Toxin-antitoxin (TA) modules are bacterial regulatory switches that facilitate conflicting outcomes for cells by promoting a pro-survival phenotypic adaptation and/or by directly mediating cell death, all through the toxin activity upon degradation of antitoxin. Intensive study has revealed specific details of TA module functions, but significant gaps remain about the molecular details of activation via antitoxin degradation used by different bacteria and in different environments. This review summarizes the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 163 publications
(216 reference statements)
6
76
0
Order By: Relevance
“…To determine the kinetics of these transcriptional responses, we subjected E. coli to two well-studied stresses, the stringent response to amino acid starvation, which can be rapidly induced via addition of serine hydroxamate (SHX), and translation inhibition, induced by treatment with chloramphenicol. Consistent with previous reports (Christensen-Dalsgaard et al, 2010;Muthuramalingam et al, 2016;Ronneau and Helaine, 2019;Shan et al, 2017), we found an increase of at least 6-fold in the mRNA levels of three type II TA systems in E. coli MG1655, mqsRA, relBE, and yefM-yoeB, at both 15 and 30 minutes after treatment using quantitative reverse transcription PCR (qRT-PCR) ( Fig. 1B-C).…”
Section: Type II Ta Systems Are Transcriptionally Induced By Diverse supporting
confidence: 92%
See 1 more Smart Citation
“…To determine the kinetics of these transcriptional responses, we subjected E. coli to two well-studied stresses, the stringent response to amino acid starvation, which can be rapidly induced via addition of serine hydroxamate (SHX), and translation inhibition, induced by treatment with chloramphenicol. Consistent with previous reports (Christensen-Dalsgaard et al, 2010;Muthuramalingam et al, 2016;Ronneau and Helaine, 2019;Shan et al, 2017), we found an increase of at least 6-fold in the mRNA levels of three type II TA systems in E. coli MG1655, mqsRA, relBE, and yefM-yoeB, at both 15 and 30 minutes after treatment using quantitative reverse transcription PCR (qRT-PCR) ( Fig. 1B-C).…”
Section: Type II Ta Systems Are Transcriptionally Induced By Diverse supporting
confidence: 92%
“…This model claimed that ppGpp promoted the accumulation of polyphosphate, which then directly stimulated Lon to degrade antitoxins, thereby liberating toxins to promote persistence. While results related to persistence were cited in a retraction of this paper, the data related to Lon activation were not and recent literature continues to invoke a connection between ppGpp and TA systems (Christensen-Dalsgaard et al, 2010;Muthuramalingam et al, 2016;Ronneau and Helaine, 2019). Thus, we wanted to test whether the stringent response and ppGpp are required for the transcriptional activation of TA systems.…”
Section: Transcriptional Induction Of Ta Systems Does Not Require Thementioning
confidence: 98%
“…Here, we examined if loss of toxins led to reduced induction of persistence following nutrient limitation or ROS, specifically NO. Indeed, we found that ΔBPSS0390 could not generate the same level of persisters after sNO exposure, whereas all three toxins had a significant reduction in persistence due to nutrient starvation (Kolodkin‐Gal, Verdiger, Shlosberg‐Fedida, & Engelberg‐Kulka, ; Muthuramalingam, White, & Bourne, ). However, further investigation is needed to determine the repertoire of stresses these toxins are responding to in macrophages.…”
Section: Discussionmentioning
confidence: 92%
“…This system induces postsegregational killing of cells that have not received such plasmid after cell division, therefore ensuring plasmid transmission to the descent. Moreover, a second module encoding a YdcE-YdcD TA system (Pellegrini et al 2005) is present in this region of the CoDiRO plasmid, whose role is to induce cells to enter in a dormant persistent state of low metabolic activity when subjected to diverse stresses (Merfa et al 2016;Muranaka et al 2012;Muthuramalingam et al 2016). An addiction module annotated by RAST as a transcriptional regulator of the ArsR family is present between the two components of the YdcE-YdcD TA system.…”
Section: Resultsmentioning
confidence: 99%